2013
DOI: 10.1371/journal.pone.0053068
|View full text |Cite
|
Sign up to set email alerts
|

CC-Chemokine Ligand 18 Induces Epithelial to Mesenchymal Transition in Lung Cancer A549 Cells and Elevates the Invasive Potential

Abstract: Lung cancer is one of the leading causes of cancer related death worldwide with more than a million deaths per year. The poor prognosis is due to its high aggressiveness and its early metastasis. Although the exact mechanisms are still unknown, the process of epithelial to mesenchymal transition (EMT) seems to be involved in these neoplastic processes. We already demonstrated that serum levels of CCL18, a primate specific chemokine, are highly elevated in patients with lung cancer and correlate with their surv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
31
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 47 publications
(36 citation statements)
references
References 30 publications
5
31
0
Order By: Relevance
“…2). This is in line with Ploenes et al who reported about an enhanced chemotaxis in lung cancer cell lines with an increased chemoresistance (20).…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…2). This is in line with Ploenes et al who reported about an enhanced chemotaxis in lung cancer cell lines with an increased chemoresistance (20).…”
Section: Discussionsupporting
confidence: 92%
“…Integrin β1 expression was upregulated in all gemcitabine-resistant sublines compared to parental cells. Integrin β4 expression was enhanced in TCC-SUP r GEMCI 20 and diminished in T24 r GEMCI 20 and in 5637 r GEMCI 20 . Comparing cisplatin-resistant cell lines, Integrin α3 expression was upregulated in 3 of 4 sublines (cisplatin-resistant sublines of T24, 5637, and TCC-SUP) and downregulated in HT1376 r CDDP…”
Section: Influence Of Acquired Chemoresistance On Chemotaxismentioning
confidence: 92%
See 1 more Smart Citation
“…In the tumor microenvironment, CCL18 promotes epithelial to mesenchymal transition in different types of solid tumors, including NSCLC (13)(14)(15). In a recently conducted study by Shi and colleagues, it was shown that CCL18 modulates NSCLC cell invasion and migration via the nitrite reductase 1-engulfment and cell motility 1/dedicator of cytokinesis 180 (NIR1-ELMO1/DOC180) pathway and thus promotes tumor metastasis (22).…”
Section: Discussionmentioning
confidence: 99%
“…CCL18 is responsible for the recruitment of naive T-cells and dendritic cells, and is capable of inducing regulatory T-cells. In the tumor microenvironment, it has been demonstrated to promote tumor spread and is believed to be one of the factors involved in the immune escape of tumor cells (13)(14)(15)(16)(17). …”
mentioning
confidence: 99%